Recurrent laryngeal nerve monitoring by flexible laryngoscopy during thyroid radiofrequency ablation in the awake patient - Teliti, Marsida; Occhini, Antonio; Fonte, Rodolfo; Croce, Laura; Calì, Benedetto; Ripepi, Federica Antonella; Carbone, Andrea; Rotondi, Mario; Chytiris, Spyridon (Frontiers in Endocrinology, 2024)
Objective: Although radiofrequency ablation (RFA) is a safe and effective non-surgical treatment for benign thyroid nodules, injury to the recurrent laryngeal nerve (RLN), is a potential and feared complication. Intermittent voice checks have been proposed to monitor vocal cord (VC) function during RFA, but such assessment is highly subjective and effort-dependent.We are here reporting the methodological use of flexible laryngoscopy (FL) for VC monitoring during bilateral thyroid RFA treatment. The patient, a 35-year-old woman, was referred to the Endocrinology Unit for subclinical hyperthyroidism due to bilateral autonomously functioning thyroid nodules.Results: At the end of the treatment of the first nodule, the FL performed by an otorhinolaryngologist specialist allowed evaluating VC function and ruling out possible paralysis before proceeding with the contralateral RFA treatment. The patient was awake during the entire procedure and well tolerated the laryngoscopic examination. The TSH serum evaluations performed one month and 9 months after the procedure assessed an euthyroid state (TSH 3.2 mIU/L and 2.8 mIU/L, respectively).During bilateral thyroid RFA the use of FL for VC monitoring treatment resulted in a safe, easy-to-perform, and effective strategy to minimize and anticipate RLN injury risk in the awake patient. The prevention of RLN damage is advisable in the case of single RFA treatment, while it should be strongly recommended when RFA is performed on bilateral nodules.